2018
DOI: 10.1007/s12024-018-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination with morphological characteristics of the skull by using 3D modeling techniques in computerized tomography

Abstract: Sex determination is a major area of investigation in forensic anthropology. As technology has advanced, imaging methods such as computed tomography and magnetic resonance imaging are being investigated as alternatives to conventional forensic anthropological research techniques. This study aimed to investigate the suitability of three-dimensional (3D) modeling of volumetric cranial computed tomography (CCT) images for sex estimation from skull morphology. In this study, CCT angiography images from the Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
15
1
5
Order By: Relevance
“…Prior work has suggested high accuracy and reliability of CT scan data relative to physical samples (e.g [ 49 , 50 , 51 , 52 ]; but see [ 53 ]). Studies have demonstrated that equivalent levels of accuracy of sex prediction can be achieved through the application of non‐metric traits to CT scan samples as what has been documented in dry skeletal material [ 49 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prior work has suggested high accuracy and reliability of CT scan data relative to physical samples (e.g [ 49 , 50 , 51 , 52 ]; but see [ 53 ]). Studies have demonstrated that equivalent levels of accuracy of sex prediction can be achieved through the application of non‐metric traits to CT scan samples as what has been documented in dry skeletal material [ 49 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research 18 has also shown no significant difference between models produced from commercial and free software. Furthermore, the precision and accuracy of 3D models produced from CT scans is well documented [19][20][21] . This capability contrasts with other professional viewing platforms which due to high costs and insufficient accessibility are not practical for research or use in a forensic science context.…”
Section: Methodsmentioning
confidence: 99%
“…These regions develop at different rates to one another Ross and Williams 2010; as well as at different rates to the rest of the body , as the viscerocranium growth is regulated by the developing paranasal air sinuses, the sensory organs and tooth eruptions (Ross and Williams 2010). The major studies which report on the viscerocranium as a whole focus mainly on the shape differences in adult samples (Chovalopoulou et al, 2017;Dereli et al, 2018). A review of the available literature revealed that there is a paucity of knowledge on the development of the entire viscerocranium in a subadult South African cohort of African ancestry.…”
Section: Introductionmentioning
confidence: 99%